A Potential Role for Exosomal Translationally Controlled Tumor Protein Export in Vascular Remodeling in Pulmonary Arterial Hypertension - Ferrer, Elisabet; Dunmore, Benjamin J.; Hassan, Dhiya; Ormiston, Mark L.; Moore, Stephen; Deighton, John; Long, Lu; Yang, Xu Dong; Stewart, Duncan J.; Morrell, Nicholas W. (American journal of respiratory cell and molecular biology, 2018)
Pulmonary arterial hypertension (PAH) is characterized by increased proliferation and resistance to apoptosis of pulmonary vascular cells. Increased expression of translationally controlled tumor protein (TCTP), a prosurvival and antiapoptotic mediator, has recently been demonstrated in patients with heritable PAH; however, its role in the pathobiology of PAH remains unclear. Silencing of TCTP in blood outgrowth endothelial cells (BOECs) isolated from control subjects led to significant changes in morphology, cytoskeletal organization, increased apoptosis, and decreased directionality during migration. Because TCTP is also localized in extracellular vesicles, we isolated BOEC-derived extracellular vesicles (exosomes and microparticles) by sequential ultracentrifugation. BOECs isolated from patients harboring BMPR2 mutations released more exosomes than those derived from control subjects in proapoptotic conditions. Furthermore, TCTP expression was significantly higher in exosomes than in microparticles, indicating that TCTP is mainly exported via exosomes. Coculture assays demonstrated that exosomes transferred TCTP from ECs to pulmonary artery smooth muscle cells, suggesting a role for endothelial-derived TCTP in conferring proliferation and apoptotic resistance. In an experimental model of PAH, rats treated with monocrotaline demonstrated increased concentrations of TCTP in the lung and plasma. Consistent with this finding, we observed increased circulating TCTP levels in patients with idiopathic PAH compared with control subjects. Therefore, our data suggest an important role for TCTP in regulating the critical vascular cell phenotypes that have been implicated in the pathobiology of PAH. In addition, this research implicates TCTP as a potential biomarker for the onset and development of PAH.